Hypothesis: ultrasonography can document dynamic in vivo rouleaux formation due to mobile phone exposure - Robert R. Brown; Robert R. Brown; Robert R. Brown; Barbara Biebrich (Frontiers in Cardiovascular Medicine)
Carrying a cellphone against the body has become commonplace in our world replete with smartphones. Acute and chronic health effects caused by these devices emitting radiofrequency radiation from multiple antennas have not been well evaluated. In this study, the popliteal vein of a healthy volunteer was imaged with ultrasonography prior to and following the placement of an idle, but active smartphone against her knee for 5 min. Pre-exposure longitudinal sonographic images demonstrate a normal anechoic lumen to the popliteal vein. Images obtained 5 min after direct skin exposure to the smartphone demonstrate a dramatic change in the acoustic appearance of the vessel. The interior of the vessel became coarsely hypoechoic with sluggish flow seen in real-time images, a typical sonographic appearance for rouleaux formation. A follow up examination performed 5 min after the subject walked around yielded continued rouleaux formation in the popliteal vein, albeit less dramatic than that observed immediately post exposure. This revolutionary in vivo method to assess radiofrequency radiation induced rouleaux formation should be further pursued in the general population to determine its prevalence and if its occurrence provides a unique biomarker of exposure that may predict morbidity.